2006
DOI: 10.1158/0008-5472.can-06-1599
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Serine-Threonine Kinase Receptor-Associated Protein Modulates the Function of Ewing Sarcoma Protein through a Novel Mechanism

Abstract: Although much is known about the oncogenic functions of chimeric Ewing sarcoma (EWS) fusion proteins that result from chromosomal translocations, the cellular role of the normal EWS protein is not well characterized. We have previously identified a WD domain-containing protein, serine-threonine kinase receptor-associated protein (STRAP), which inhibits transforming growth factor B (TGF-B) signaling through interaction with receptors and Smad7 and promotes growth and enhances tumorigenicity. Here, we report the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
(56 reference statements)
0
35
0
Order By: Relevance
“…Moreover, our studies provide evidence as to how the NM23-H1 tumor suppressor cooperates with the p53 tumor suppressor to mediate its suppressive effect on tumor progression. We also demonstrate that, in addition to its proposed oncogenic function (27), STRAP can exert a tumor suppressor effect by activating the function of p53.…”
Section: Nm23-h1 and Strap Stimulate P53 Activity By The Removal Of Mmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, our studies provide evidence as to how the NM23-H1 tumor suppressor cooperates with the p53 tumor suppressor to mediate its suppressive effect on tumor progression. We also demonstrate that, in addition to its proposed oncogenic function (27), STRAP can exert a tumor suppressor effect by activating the function of p53.…”
Section: Nm23-h1 and Strap Stimulate P53 Activity By The Removal Of Mmentioning
confidence: 56%
“…Recent studies also suggest that STRAP might be involved in tumorigenesis and development (26,27). We have recently reported that STRAP-induced inhibition of TGF-␤ signaling was enhanced by direct interaction with the NM23-H1 tumor suppressor, suggesting a possible link between TGF-␤-and NM23-H1-mediated signaling pathways (28).…”
mentioning
confidence: 96%
“…Proteolytic fragments from MBP-xMcm10-His 6 were excised from the SDS-PAGE gel and subjected to in-gel digestion with Trypsin Gold (Promega) using standard procedures (32). The resulting peptides were analyzed by matrix-assisted laser desorption/ionization, time-of-flight mass spectrometry (MALDI-TOF MS) and TOF/TOF tandem MS using a Voyager 4700 (Applied Biosciences, Framingham MA).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, in addition to these Ub ligases, adaptor proteins like STRAP, the stabilizer of Smad7-TGFb receptor complexes, can also be misexpressed in human colon and lung cancers [97]. The oncogenic role of STRAP though, in addition to acting as a TGFb receptor inhibitor, can be due to its ability to interact with nuclear oncogenes like the Ewing sarcoma (EWS) oncoprotein [98].…”
Section: Relevance Of Stability Regulation Of Tgfβ Pathway Componentsmentioning
confidence: 99%